Quality evaluation of KAU red rice (oryza sativa L.) varieties - Revathy G Nadh (Department of Community Science, College of Horticulture, 2018)
The present study entitled " Quality evaluation of KAU red rice (Oryza sativa L.) varieties was conducted with the objective to assess the effect of parboiling on the physical, biochemical, nutritional, cooking and organoleptic qualities of KAU red rice varieties. The study also aimed to assess the suitability of these rice varieties for the preparation of selected traditional food products. Milling per cent among raw red rice varieties varied from 62.76 per cent (Aathira) to 76 (Ezhome-4) per cent and in parboiled samples ranged from 67.66 per cent (Aiswarya) to 77.33 (Ezhome-4) per cent. The highest milling per cent was observed in Ezhome-4 both raw and parboiled samples. An increase in milling per cent was observed in all the varieties after parboiling. Among red rice varieties head rice recovery ranged from 49.32 per cent (Aiswarya) to 59.15 per cent (Ezhome-4) per cent in raw samples. In parboiled samples the highest head rice recovery was observed in Ezhome-4 (62.86%) and the lowest was in control variety Jyothi (53.66%). There was no significant variation among red rice varieties in thousand grain weight and were comparable with Jyothi. In parboiled samples an increase in thousand grain weight was observed. Among raw red rice varieties volume weight ranged from 13.87mm3 (Aathira) to 11.84mm3 (Aiswarya). The highest volume weight in parboiled samples was observed in Aathira (14.17mm3) and the lowest was in Samyuktha (11.93mm3). Among red rice varieties the highest L/B ratio 3.24 and 2.98 was observed in control variety Jyothi both raw and parboiled samples. All the selected varieties were of lower grain length than control variety Jyothi. All varieties showed an increase in major physical quality parameters after parboiling. In raw red rice varieties the highest bulk density of 0.72g/ml was observed in varieties Aathira and Ezhome-4. In the case of parboiled samples highest bulk density was observed in Kanchana (0.66g/ml). Water absorption index in raw red rice flour was found to be highest in Aiswarya (25.61) and the lowest was in Samyuktha (22.46). In parboiled rice flour the highest water absorption index was observed in Aathira (23.71) and the lowest was in Ezhome-4 (22.04). In raw red rice flours, water solubility index in the range of 0.45 (Aathira) to 0.57(Ezhome-4). The highest water solubility index of 0.61 was observed in Ezhome-4 in parboiled samples and the lowest was in control variety Jyothi (0.54). The highest syneresis per cent was observed in Samyuktha after 12th day of study in both raw and parboiled samples. In raw samples Samyuktha showed a low gelatinisation temperature index. Varieties Ezhome-4, Aathira, Jyothi, Kanchana and Aiswarya showed intermediate gelatinisation temperature index. In parboiled samples, all six varieties shown intermediate gelatinization temperature as the grains were swollen and collar incomplete and narrow. The cooking time taken by the rice varieties varied from 20.33 minutes (Samyuktha) to 27 minutes (Ezhome-4) in raw samples. In parboiled varieties, cooking time increased which varied from 28.33 minutes (Samyuktha) to 37.66 minutes (Aiswarya). In raw red rice varieties water uptake was in the range of 8.71ml (Ezhome-4) to 7.39ml (Samyuktha). In parboiled samples an increase in water uptake was observed with the highest in Ezhome-4 (12.80ml) variety and lowest in Samyuktha (8.83ml) variety. Volume expansion in raw samples ranged from 5.43 (Ezhome-4) to 4.38 (Aiswarya). In parboiled samples it was ranged from 5.70 (Jyothi) to 4.77 (Samyuktha). The highest amylose content of 24.90 per cent was observed in Aathira and the lowest was in Samyuktha (23.23%) in raw red rice varieties. Among parboiled rice varieties highest amylose content was observed in Ezhome-4 (24.54%) and the lowest was in Samyuktha (23.03%). Gel length of different raw samples ranged from 62.21mm (Kanchana) to 55.76mm (Ezhome-4). In parboiled samples it was ranged from 51.33mm (Aiswarya) to 24.66mm in control variety Jyothi. In raw samples grain elongation ratio was varied from1.47 (Samyuktha) to 1.79 (Aiswarya). No significant variation in grain elongation ratio was observed. A decrease in grain elongation ratio was observed in parboiled samples with the highest in Kanchana (1.61) and the lowest in Samyuktha (1.43). The highest moisture content in raw rice was observed in Aiswarya (12.5%) and the lowest was in Jyothi (10.5%). The highest moisture content in parboiled samples was observed in Aiswarya (11.56%) rice variety and the lowest was in control variety Jyothi (9.70%). In raw samples starch content was varied from 70.50g/100(Aiswarya) to 65.83 (Jyothi). In parboiled samples it was ranged from 67.43g/100g (Ezhome-4) to 62.40g/100g (Kanchana). Among raw red rice varieties highest protein was observed in Ezhome-4 (5.50g/100g) and the lowest was in Samyuktha (4.70g/100g). The highest protein content in parboiled samples was noticed in Samyuktha (3.75g/100g) rice variety and the lowest was in control variety Jyothi (3.12g/100g). The fat content of different raw samples was in the range of 0.24/100g (Samyuktha) to 0.35g/100g (Aathira). Among parboiled samples the highest fat content was observed in Aathira rice variety (0.48g/100g) and the lowest was in Samyuktha (0.31g/100g). In raw samples highest fibre content of 0.31g/100g was noticed in Ezhome-4 and Samyuktha. The control variety Jyothi obtained lowest fibre content in both raw and parboiled samples. The highest thiamine content in raw rice varieties was reported in Aiswarya (0.08mg/100g) and the lowest of 0.06 was recorded in control variety Jyothi and Samyuktha (0.060mg/100g). In parboiled samples the highest thiamine content was observed in control variety Jyothi (0.087mg) and the lowest was in Samyuktha (0.070mg/100g). The calcium content of raw rice varieties was determined and found that the highest calcium content was observed in Kanchana (5.76mg/100g) and the lowest was in Aiswarya (4.90mg/100g). The highest calcium content in parboiled samples was reported in Kanchana (6.06mg/100g) and the lowest was in Ezhome-4 (5.50mg/100g). Among raw red rice varieties the highest zinc content was observed in Aathira (1.32mg/100g) and Kanchana (1.32mg/100g) and the lowest was in control variety Jyothi (1.09mg/100g). In parboiled rice varieties, the highest zinc content was noticed in Samyuktha (1.35mg/100g) and the lowest was in Jyothi (1.25mg/100g). In both raw and parboiled samples highest iron content of 0.61mg/100g and 0.65mg/100g was observed in control variety Jyothi and the lowest of 0.39mg/100g and 0.43mg/100 was observed in Kanchana rice variety. The phosphorus content of raw red rice varieties was estimated and found that the highest value was observed in Aiswarya (131.96mg/100g) and the lowest was in Aathira (127.60mg/100g). In parboiled samples the highest was reported in Aiswarya (132.60mg/100g) and the lowest of 129.93 was observed in Aathira variety. The highest in vitro digestibility in raw rice varieties was observed in Aathira (79.06%) and the lowest was in Ezhome-4 (72.46%). The highest starch digestibility in parboiled samples was noticed in Aathira (76.16%) and the lowest was in Ezhome-4 (70.06%). The bran oil content of rice varieties was assessed and found that among raw red rice varieties the highest oil content was noticed in Samyuktha (2.10g) and the lowest was in control variety Jyothi (1.26g). In parboiled samples the highest oil content was observed in Aathira (2.16g) and the lowest was in Aiswarya (1.86g) and control variety Jyothi (1.86g). From organoleptic evaluation of products it was found that all the selected varieties were suitable for table rice. Rice variety Kanchana was found to be the most suitable variety for the preparation of idli. For the preparation of idiyappam Ezhome-4 was found to be the most suitable variety. From the present study it was found that quality attributes of selected red rice varieties were comparable with control variety Jyothi. All the varieties showed an increase in physical quality parameters after parboiling. All the selected red rice varieties are suitable for the preparation of traditional food products. The information on grain quality characteristics can be utilised to popularise these red rice varieties specifying the product suitability.